1989
DOI: 10.1523/jneurosci.09-03-00898.1989
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of the hippocampal formation but not lesions of the fornix or the mammillary nuclei produce long-lasting memory impairment in monkeys

Abstract: A group of tasks sensitive to human amnesia were used to characterize the severity and duration of memory impairment in monkeys following bilateral damage to the hippocampal formation, fornix, or mammillary nuclei. Monkeys with hippocampal formation lesions (which included the hippocampus proper, dentate gyrus, subiculum, posterior entorhinal cortex, and much of the parahippocampal gyrus) exhibited a substantial and lasting memory impairment. Monkeys with fornix transection or bilateral damage to the mammillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
140
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(153 citation statements)
references
References 51 publications
11
140
0
2
Order By: Relevance
“…been shown to decrease delay-related firing in PFC neurons (Fuster 1973). Performance following the longest delays in this study likely involved prefrontal cortex interactions with hippocampal and medial temporal cortical regions, as the hippocampal complex is needed for delays greater than 10 seconds (Zola-Morgan et al 1989). The finding that clonidine did not differentially improve performance at long delays argues against drug actions in the medial temporal lobe.…”
Section: Delay Analysismentioning
confidence: 54%
“…been shown to decrease delay-related firing in PFC neurons (Fuster 1973). Performance following the longest delays in this study likely involved prefrontal cortex interactions with hippocampal and medial temporal cortical regions, as the hippocampal complex is needed for delays greater than 10 seconds (Zola-Morgan et al 1989). The finding that clonidine did not differentially improve performance at long delays argues against drug actions in the medial temporal lobe.…”
Section: Delay Analysismentioning
confidence: 54%
“…This tract provides the major route from the hippocampal formation to the medial diencephalon. The various studies have reported either mild impairments (e.g., Saunders 1983; Gaffan 1994a), or no apparent deficit (e.g., Bachevalier et al 1985a,b;Zola-Morgan et al 1989;Charles et al 2004) following fornix lesions. It is evident (Fig.…”
Section: Nonhuman Primatesmentioning
confidence: 99%
“…This suggests that the hippocampus plays a critical role in memory processes and that the hippocampal integrity is affected during normal aging. Aged non-human primates performed poorly compared to young monkeys on a number of tasks that are sensitive to deficits in memory (e.g., delayed response and delayed non-match to sample) [5,21,23,26,27,36,38]. Deficits on those tasks, which are sensitive to aging in monkeys, are produced by damage to the prefrontal cortex and the medial temporal lobe, including the hippocampus [5,21,27].…”
Section: Introductionmentioning
confidence: 99%